Intermittent Boluses of Local Anesthetic Through Quadratus Lumborum Catheters for Analgesia in a Living Donor Hepatectomy - Shelly B. Borden; Molly K. Groose; Eric R. Simon; Aaron S. Hess; Kristopher M. Schroeder (Case Reports in Anesthesiology)
The demand for liver transplants in the United States far exceeds the supply of organs. As need has increased, so has use of living donors. Coagulopathy and various side effects often preclude the use of neuraxial regional techniques and opioids for postoperative analgesia in patients with large “J” incisions. Here, we present a 25-year-old male undergoing a living donor hepatectomy who received quadratus lumborum catheters placed percutaneously after closure of incision and prior to emergence to provide excellent analgesia and a viable opioid-sparing approach. Quadratus lumborum catheters are a safe option for a multimodal, opioid-sparing approach to analgesia.